Late-life deficits in cognitive, physical and emotional functions, childhood intelligence and occupational profile: a life-course examination of the Aberdeen 1936 Birth Cohort (ABC1936) - Chapko, Dorota (Age Ageing, 2016)
Objectives: the ‘triad of impairment’ phenomenon describes the co-occurrence of age-related cognitive, emotional and physical functioning deficits. We investigated how occupational profile and childhood intelligence contribute to the triad of impairment in late life. Methods: we analysed data of a subsample of the Aberdeen Birth Cohort of 1936 (n = 346). Data were collected on participants' childhood intelligence, late-life cognitive ability, physical functioning, depressive symptoms and main lifetime occupation. We summarised the various occupational and impairment measures into two latent variables, ‘occupational profile’ and the ‘triad of impairment’. We used a series of data reduction approaches and structural equation models (SEMs) of increasing complexity to test both the validity of the models and to understand causal relationships between the life-course risks for the triad of impairment. Results: occupational profile had a significant effect on the triad of impairment independent of childhood intelligence. Childhood intelligence was the predominant influence on the triad of impairment and exerted its effect directly and indirectly via its influence on occupation. The direct effect of childhood intelligence exceeded the independent influence of the occupational profile on impairment by a factor of 1.7–1.8 and was greater by a factor of ∼4 from the indirect pathway (via occupation). Conclusions: childhood intelligence was the predominant influence on the triad of impairment in late life, independently of the occupational profile. Efforts to reduce impairment in older adults should be informed by a life-course approach with special attention to the early-life environment.